Cytotoxicity Potential of Endophytic Fungi Extracts from Terminalia catappa against Human Cervical Cancer Cells - Michèle Stella Majoumouo; Marius Belmondo Tincho; Rufin Marie Kouipou Toghueo; Thureyah Morris; Donavon Charles Hiss; Fabrice Fekam Boyom; Chitra Mandal (Journal of Toxicology)
Endophytic fungi are potential sources of novel bioactive metabolites from a natural product drug discovery perspective. This study reports the bioactivity-directed fractionation of the secondary metabolites of the ethyl acetate extract of a fermentation culture of endophytic fungi from Terminalia catappa which were then evaluated for their cytotoxicity against human cervical cancer (HeLa) cells and human foreskin fibroblast (HFF) cells. Furthermore, apoptosis was determined using the Annexin V/propidium iodide (PI) flow cytometry assay. Endophyte extracts N2, N7, N8, N97, N169, and N233 were obtained from Trichoderma sp, Phoma sp, Phomopsis phyllanticola, Fusarium oxyporum, Collectotrichum sp, and Cryptococcus flavescens, respectively. The N97 extract was most active with a 50% inhibitory concentration (IC50) of 33.35 µg/ml. A 50% cytotoxic concentration (CC50) of 268.4 µg/ml was obtained with HFF cells and the selectivity index (SI) was 8.01. The percentages of cell populations were increased at late apoptosis (Annexin+/PI+), with the percentages of 27.4 ± 0.3 and 19.2 ± 0.01 obtained, respectively, for 50 µg/ml and 80 µg/ml of the N97 extract and 2.1 ± 0.1 obtained for the control in late apoptosis (Annexin V+/PI+) . Moreover, a higher reduction in the percentage of viable cells was observed in the HeLa control cells (93.6 ± 0.3), but the percentages of viable HeLa cells were 37 ± 0.05 and 45 ± 0.1, respectively, for the 50 µg/ml and 80 µg/ml treatments with the N97 extract. Also, the percentages of 34.7 ± 0.1 and 33.9 ± 0.4 were, respectively, obtained for 50 µg/ml and 80 µg/ml compared to the control with 4.6 ± 0.2, in early apoptosis (Annexin V+/PI-). These findings highlight the anticancer potential of the N97 extract of endophytic fungi from Terminalia catappa, which is mediated through apoptosis and presumably also attenuation of chemoresistance.